Pendugaan Reliability Waduk Nadra Krenceng PT. Krakatau Tirta Industri - Wirasembada, Yanuar Chandra; Saptomo, Satyanto Krido; Saputra, Muhamad Budi (Jurnal Teknik Sipil dan Lingkungan, 2016)
The increasing of high population rate, plus there was a new steel industry named PT. Krakatau Posco in Cilegon has made higher demand of  clean and raw water. The Volume of Nadra Krenceng reservoir used by PT. Krakatau Tirta Industri is still doubted to fulfill water demand in Cilegon. The purpose of this research  to analyze how much the reservoir volume capacity that will always be available and makes the program with Visual Basic Application in Microsoft Excel. The reliability calculation of Nadra Krenceng reservoir was conducted using three methods; F.J Mock, NRECA dependable discharge, and simulation the result of both methods use Weibull Method. The simulation result of Weibull Method shows for F.J Mock dependable discharge with probability of 95%, 90%, 80% and 50% are 5,023,095 m3; 5,733,905 m3; 7,215,525 m3; and 11,600,385 m3 respectively. For NRECA Method simulation, the result with the same series probabilities are 3,831,718 m3; 4,531,326 m3; 5,930,542 m3; and 10,128,191 m3 respectively. The Probabilities used by PT. KTI to guarantee the water availability in Nadra Krenceng reservoir is 80%. To conclude, the available volume of Nadra Krenceng reservoir now 7,215,525 m3 for F.J Mock Method and 5,930,542 m3 for NRECA Method. Both of calculation of water availability of Nadra Krenceng reservoir could achieve good enough accuracy. The R2 values for F.J Mock Methods is 0.685 and 0.653 for NRECA method.